Quenching and Recovery of Persistent X-Ray Emission during a Superburst in 4U 1820–30 - Zhijiao Peng; Zhaosheng Li; Yuanyue Pan; Tao Fu; Wenhui Yu; Yupeng Chen; Shu Zhang; Maurizio Falanga; Shuang-Nan Zhang (The Astrophysical Journal)
We report the superburst from 4U 1820–30 in 2021 observed by the Monitor of All-sky X-ray Image and Neutron star Interior Composition Explorer (NICER). During the tail of the superburst, we found that the NICER light curve unexpectedly increased from 1080 to 2204 counts s ^−1 over 6.89 hr. From the time-resolved superburst spectra, we estimated the burst decay time of ≈2.5 hr, the ignition column depth of ≈0.3 × 10 ^12 g cm ^−2 , the energy release per unit mass of ≈2.4 × 10 ^17 erg g ^−1 , the fluence of ≈4.1 × 10 ^−4 erg cm ^−2 , and the total energy release of ≈3.5 × 10 ^42 erg. Notably, we found a gradual increase in the Comptonization flux from 8.9 × 10 ^−10 erg s ^−1 cm ^−2 to the preburst level during the superburst. This increase can be interpreted as a consequence of superburst radiation depleting the inner accretion disk, leading to a near-complete quenching of the persistent emission. As the burst radiation decayed, the inner accretion disk gradually returned to its preburst state, as evidenced by the best-fit spectral parameters. Additionally, we observed a prominent absorption line that exhibited a gravitational redshift, shifting from 4.15 to 3.62 keV during the recovery phase of persistent emission. This absorption feature likely originates from the inner accretion disk rather than from burst emission on the neutron star (NS) surface. The observed changes in the absorption line energy suggest that the inner disk approached the NS to a distance as close as ≈17 km.